Analysis of the Role of Spiritual Well-Being on Ethical Judgment Among Accounting Students - Rosdiana, Siti; Junaidi, Junaidi; Anwar, Suhardi M.; Sahrir, Sahrir (Nominal: Barometer Riset Akuntansi dan Manajemen, 2025)
The purpose of this study was to determine how the spiritual well-being (SWB) variable as a personal factor affects the ethical judgment of accounting students both directly and through mediating variables such as materialism, ethical ideology, and ethical beliefs. Structural Equation Modeling (SEM) was used to test the research hypothesis model. A total of 288 survey data were collected from accounting students from universities in Sulawesi and outside Sulawesi. The results showed that the variables of spiritual well-being and ethical ideology and ethical beliefs of accounting students have a positive and significant relationship; however, the variables of spiritual well-being and materialism show an insignificant relationship. The moral factors of ethical ideology and ethical beliefs of accounting students show a positive and significant influence on ethical considerations; the materialism variable is rejected because it shows an insignificant relationship to students' ethical judgments. The implications of this study are that it can be a reference for further researchers related to the proposed variables. Keywords: Spiritual Well-Being, Ethical Ideology, Ethical Judgment, Accounting, SEM ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui bagaimana variabel kesejahteraan spiritual (SWB) sebagai faktor pribadi mempengaruhi penilaian etis mahasiswa akuntansi baik secara langsung maupun melalui variabel mediasi seperti materialisme, ideologi etika, dan keyakinan etika. Structural Equation Modeling (SEM) digunakan untuk menguji model hipotesis penelitian. Sebanyak 288 data survei dikumpulkan dari mahasiswa akuntansi dari universitas di Sulawesi dan di luar Sulawesi. Hasil penelitian menunjukkan bahwa variabel kesejahteraan spiritual dan ideologi etika serta keyakinan etika mahasiswa akuntansi memiliki hubungan yang positif dan signifikan; namun, variabel kesejahteraan spiritual dan materialisme menunjukkan hubungan yang tidak signifikan. Faktor moral ideologi etika dan keyakinan etika mahasiswa akuntansi menunjukkan pengaruh positif dan signifikan terhadap pertimbangan etis; variabel materialisme ditolak karena menunjukkan hubungan yang tidak signifikan terhadap penilaian etis siswa. Implikasi dari penelitian ini adalah dapat menjadi dasar acuan untuk peneliti selanjutnya yang berkaitan dengan variabel diajukan. Kata Kunci: Kesejahteraan Spiritual, Ideologi Etis, Penilaian Etis, Akuntansi, SEM